Correlation between allopregnanolone levels and depressive symptoms during late menopausal transition and early postmenopause. (1st February 2018) - Slopien, Radoslaw; Pluchino, Nicola; Warenik-Szymankiewicz, Alina; Sajdak, Stefan; Luisi, Michele; Drakopoulos, Panagiotis; Genazzani, Andrea R.
Abstract: Objectives: This observational, cross-sectional study included 140 women with climacteric symptoms. The aim of the study was to evaluate the correlation between the presence and severity of depressive symptoms and allopregnanolone levels in women during late menopausal transition and early postmenopause. Methods: The study group was divided into two groups: 45 women in late menopausal transition and 95 early postmenopausal women. We evaluated Kupperman index, Hamilton scale and serum follicle-stimulating hormone, luteinizing hormone, 17β-estradiol, prolactin, total testosterone, dehydroepiandrosterone sulfate and allopregnanolone levels. Results: We found that serum allopregnanolone concentration was lower in early postmenopausal women compared to women in late menopausal transition; that there was a correlation between serum allopregnanolone levels in early postmenopausal women and time since last menstruation, intensity of climacteric symptoms, and intensity of depression symptoms and that there was a correlation between serum allopregnanolone levels and several depression symptoms presence (shallow sleep and symptoms of the digestive tract in women during late menopause transition; feelings of guilt, sleep disorders and general somatic symptoms in early postmenopausal women). Conclusion: We concluded that reproductive aging is characterized by a reduction of allopregnanolone circulating levels that correlate to Hamilton depression index in early postmenopause and presence of specific depressive symptoms during late menopausal transition and early postmenopause.